Detection of ESBL/AmpC-Producing and Fosfomycin-Resistant Escherichia coli From Different Sources in Poultry Production in Southern Brazil - Gazal, Luís Eduardo de Souza; Medeiros, Leonardo Pinto; Dibo, Miriam; Nishio, Erick Kenji; Koga, Vanessa Lumi; Gonçalves, Bruna Carolina; Grassotti, Tiela Trapp; de Camargo, Taiara Carolaine Leal; Pinheiro, João Juliano; Vespero, Eliana Carolina; de Brito, Kelly Cristina Tagliari; de Brito, Benito Guimarães; et al. (Frontiers in Microbiology, 2021)
This study discussed the use of antimicrobials in the commercial chicken production system and the possible factors influencing the presence of ESBL/AmpC producers strains in the broiler production chain. The aim of this study was to perform longitudinal monitoring of ESBL-producing and fosfomycin-resistant E. coli from poultry farms in southern Brazil (Paraná and Rio Grande do Sul states) and determine the possible critical points that may be reservoirs for these strains. Samples of poultry litter, cloacal swabs, poultry feed, water, and beetles (Alphitobius sp.) were collected during three distinct samplings. Phenotypic and genotypic tests were performed for characterization of antimicrobial resistant strains. A total of 117 strains were isolated and 78 (66%) were positive for ESBL production. The poultry litter presented ESBL positive strains in all three sampled periods, whereas the cloacal swab presented positive strains only from the second period. The poultry litter represents a significant risk factor mainly at the beginning poultry production (odds ratio 6.43, 95% confidence interval 1 – 41.21, p < 0.05). All beetles presented ESBL positive strains. The predominant gene was blaCTX-M group 2, which occurred in approximately 55% of the ESBL-producing E. coli. The cit gene was found in approximately 13% of the ESBL-producing E. coli as AmpC type determinants. A total of 19 out of 26 fosfomycin-resistant strains showed the fosA3 gene, all of which produced ESBL. The correlation between fosA3 and blaCTX-M group 1 (blaCTX-M55) genes was significant among ESBL-producing E. coli isolated from Paraná (OR 3.66, 95% CI 1.9 - 9.68) and these genetic determinants can be transmitted by conjugation to broiler chicken microbiota strains. Our data revealed that poultry litter and beetles were critical points during poultry production and the presence of fosfomycin-resistant strains indicate the possibility of risks associated with the use of this antimicrobial during production. Furthermore, the genetic determinants encoding CTX-M and fosA3 enzymes can be transferred to E. coli strains from broiler chicken microbiota, thereby creating a risk to public health. This work was supported by the Bill & Melinda Gates Foundation, Grant Number INV-007641